Characterization of dairy goat farming in Western Cariri, Semi-arid region of Paraiba, Northeast Brazil (Research, Society and Development, 2022)
The objective of the present study was to carry out the characterization of dairy goats in two Immediate Geographic Regions (IGR) belonging to the semiarid region of Paraíba in the Northeast of Brazil. The study was carried out between december 2020 and january 2021 with visits to 150 goat farms in the IGR’s of Monteiro (n= 70) and Sumé (n= 80), both belonging to the state of Paraíba. During the visits, questionnaires were applied with objective questions to the producer or responsible, in order to verify data associated with the owner, property, herd, hygienic-sanitary, nutritional and reproductive management. The educational level in the properties 80% (n= 120) studied beyond the elementary level. The size of properties in 65.4% (n=98) was greater than 50 ha. It was observed that there is a predominance of 93.4% (n= 140) of the properties in the two IGR's studied of semi-intensive breeding, with 78% (n= 117) carrying out the exploitation of animals for breeding. Most properties had herds with more than sixty animals (98%, n= 147), with an average production of more than sixty liters/day (72%, n= 108). The results obtained allow us to conclude that the profile of the properties studied in the IGR’s of Monteiro and Sumé are characterized by properties with an area greater than 50 ha, with low technological level, lack of technical assistance in a significant amount, and training that allow a better profitability of production. Therefore, it is suggested that these aspects should be taken into account when planning the future development of public policies for a better development of goat farming in these regions.